“KARYSTÍA LÍTHOS”: A TIMELESS STRUCTURAL ORNAMENTAL STONE - Laskaridis, K.; Patronis, M. (Bulletin of the Geological Society of Greece, 2010)
Karystía Líthos (= Stone of Karystos) is a widely used structural material since archaic times. It has been used in various constructions, considered to date before 700 BC or before the Trojan War or even as early as the Neolithic Age. The term “Karystía Líthos”, mentioned by Strabo, Pliny et al., includes cipollino marble, slates etc. Their main mineralogical constituent is calcite and their colour depends on the secondary and accessory minerals. This paper examines the timelessness of Karystía Líthos, focusing on the determination of its physical - mechanical and aesthetic characteristics. The natural stone properties are classified into those characterizing the material, and those determining the suitability of the stone for various special uses. Those properties were determined according to Standard EN 12326-2 “Slate and stone products for discontinuous roofing and cladding - Part 2: Methods of test”. The results were statistically analyzed, in order to draw relevant practical conclusions. The physical - mechanical properties of Karystía Líthos, on which its endurance through time and under mechanical stresses is depending, and its aesthetics, render it a widely applied ornamental stone to-date.